MODERNISTIC RESEARCH IN THE STORIES OF ULUGHBEK HAMDAM - Norova Khilola Ismoilovna (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Abstract: This article analyzes the stories of Ulugbek Hamdam in terms of modernist research. The stories describe the author's achievements and skills in depicting the spiritual world and psyche of a person. Modernism is a complex philosophical-aesthetic phenomenon that arose as a result of significant changes in the social, political, psychological, philosophical, artistic and aesthetic thinking of the writer. These changes, in a certain sense, reject existing traditions in the form of artistic expression. The symbolism, philosophical observations, and peculiarities in the depiction of the hero and reality expressed in such stories as "The Man with His Eyes Opened", "The Muslim", "The Island of Statues", "A Cup of Water", "Pillapoya", "The Story of the Full Moon" are analyzed as a product of the author's new research.